New constitutive equation for salt rock creep - Motta,Gabriel Esteves (2014)
Drilling and stabilizing oil wells are important technological challenges for developing the Brazilian Pre-Salt deposits due to creep behaviour of salt rocks, which results in well closure and collapse. The objectives of this work are to analyse the currently used creep models and to propose a new empirical model that comprehends the three creep stages. This work suggests that a deep interpretation of Burger's rheological model, based on the physical parameters of creep phenomenon, should be investigated. The problem of the explicit presence of time in creep strain rate models is discussed. The new proposed model is able to reproduce models that describe the transient and the steady-state creep stages. However, its calibration should be careful, based on data from all these creep stages.